2013
DOI: 10.1182/blood-2012-10-463414
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes promote murine osteoblastic HSC niche expansion and stem cell engraftment after radioablative conditioning

Abstract: • After radioablative conditioning, host megakaryocytes promote endosteal HSC niche expansion and donor stem cell engraftment.• Thrombopoietin administration before radiation and bone marrow transplant enhances megakaryocyte promotion of HSC engraftment.Successful hematopoietic stem cell (HSC) transplantation requires donor HSC engraftment within specialized bone marrow microenvironments known as HSC niches. We have previously reported a profound remodeling of the endosteal osteoblastic HSC niche after total b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 38 publications
1
124
1
Order By: Relevance
“…[55][56][57][58] Two recent studies 59,60 have demonstrated that megakaryocytes likely contribute to the HSC niche because in vivo megakaryocyte ablation results in a loss of HSC quiescence. Because HSCs are proximal to megakaryocytes in the bone marrow and because BLOOD, 10 MARCH 2016 x VOLUME 127, NUMBER 10 EARLY STEM CELL-TO-MEGAKARYOCYTE TRANSITION 1245…”
Section: Megakaryocytes In the Hematopoietic Stem Cell Nichementioning
confidence: 99%
“…[55][56][57][58] Two recent studies 59,60 have demonstrated that megakaryocytes likely contribute to the HSC niche because in vivo megakaryocyte ablation results in a loss of HSC quiescence. Because HSCs are proximal to megakaryocytes in the bone marrow and because BLOOD, 10 MARCH 2016 x VOLUME 127, NUMBER 10 EARLY STEM CELL-TO-MEGAKARYOCYTE TRANSITION 1245…”
Section: Megakaryocytes In the Hematopoietic Stem Cell Nichementioning
confidence: 99%
“…52 TPO administration before TBI enhances megakaryocyte-induced promotion of HSC engraftment. 53 One study showed that TPO can activate NF-kB in megakaryocytes. 54 It is intriguing that the same signaling pathway involving Iex-1, NF-kB, and Erk activation could be triggered by Mpl/TPO to protect both HSCs and megakaryocytes from TBI.…”
Section: Kitmentioning
confidence: 99%
“…After transplantation, HSCs home to Mk-rich endosteal areas [12][13][14] , and host Mk facilitate donor HSC engraftment after lethal irradiation 13 . In addition, co-culture with Mk slightly increased HSC numbers ex vivo 14 .…”
mentioning
confidence: 99%